Characteristics of Board of Directors and Cost of Debts: A Case of United Arab Emirates Listed Companies - Aomrah, Muneer Rajab Awadh (2011)
Cost of debt provides signals not only on how the firms are financed but it also indicates managers’ ability to increase the bottom line-income statement item. Thus, with a good corporate governance practice, firms are expected to experience optimum level of cost of debt. However, there is a general lack of studies that investigate this issue in the Gulf Council Countries (GCC), particularly the United Arab Emirates (UAE). Therefore, this research is conducted to investigate the relationship between characteristics of board of directors and cost of debts in UAE setting. The characteristics tested include board size, board independence, duality, board meetings, multiple directorships and major director ownership. This paper reports the results from a multivariate analysis on a dataset collected from the 2009 company annual reports of 62 non-financial UAE companies listed on the Dubai Financial Market and Abu–Dhabi Securities Exchange. The empirical results of this study found that the relationship between board size and board independence with cost of debts was in a negative direction but not significant. However, the results found that there was a positive relationship between CEO duality and cost of debts. Board meetings and multiple directorships of the board were the new variables discussed by this study, and the results found that there was a negative relationship between board meetings and multiple directorships with cost of debts. Although, the results of this study found a negative relationship between major director ownership and cost of debts, this relationship was not significant statistically.